Soft tissue Reconstruction of Gustilo-Anderson Grade IIIB Open Extra-Articular Tibial Fractures at a Tertiary Hospital in Cape Town, South Africa: A Retrospective Case Series - Barouni, Elyas (Division of Plastic and Reconstructive Surgery, 2021)
Introduction: Management of Gustilo-Anderson grade 3b tibia fractures are challenging due to the high rate of complications which includes infection, nonunion and possible amputation. Due to limited soft tissue coverage of the tibia antero-medially, open fractures remain a treatment challenge. Despite many advances, the ideal time delay to definitive soft tissue cover remains controversial. Aim: We aimed to investigate the management strategy and the outcome of soft tissue reconstruction of Gustilo-Anderson grade 3b tibia fractures at a tertiary hospital in Cape Town, South Africa. Methods: A retrospective study was conducted on 22 patients who underwent soft tissue reconstruction for grade 3b tibia fractures from January 2014 to July 2017. Patient demographics, comorbidities, injury characteristics and management practices such as time to debridement, relook time, Negative Pressure Wound Therapy (NPWT), soft tissue coverage and complications were recorded. Results: Most patients were males (n=18; 81.8%) with an average age of 39.3 years. Pedestrian vehicle accidents accounted for 45.4%(n=10), motor-vehicle accidents (n=6; 27.3%) and gunshot wounds (n=2; 9.1%). The commonest site of injury was the middle third of the tibia (n=13; 59.1%), distal third (n=7; 31.8%) and proximal third (n=2; 9.1%). Most patients (n=18; 81.8%) were debrided within 24 hours. The mean times for NPWT prior to cover was 12.5 days and for soft tissue cover 13.7 days (range 2-35), respectively. Fasciocutaneous flaps (n=11; 50%) were predominantly used as cover, then pedicled muscle flaps (n=8; 36.4%), free flaps (n=2) and skin graft(n=1). Most patients (n=13; 59.1%) received satisfactory outcomes. Seven (31.8%) required soft tissue revisions. Three patients (13.6%) suffered complications namely, complete flap loss resulting in amputation, partial skin graft loss and soft tissue infection, respectively. Patients who underwent debridement after 24 hours reported the least complications and there appeared to be better outcomes in the relooks beyond 48 hours. Conclusion: Despite achieving outcomes which concur with other published studies, the BOAST 4 guidelines were not fully reflected in our management strategy. We will require larger numbers in future studies to formulate a standardized management protocol going forward.